Virtual reference best practices tailoring services to your library - Kern, M. Kathleen; IG Publishing (Chicago American Library Association, 2009)
When it comes to virtual reference, one size doesn't fit all. What works in one library won't necessarily work in another. How do you figure out what to do? The recently published Virtual Reference Service Guidelines from the Reference and User Services Association (RUSA), which is reproduced in appendix A, provides the starting point. Kern, a leading virtual reference expert, outlines the tools and decision-making processes that will help you and your library evaluate, tailor, and launch virtual reference services that are a perfect fit for your community and your library.
Defining virtual reference -- Implementing virtual reference : is it the right thing, right now? -- Who are we doing this for? -- Buy-in : gaining commitment and support -- Policies : setting expectations of who, when, and what -- Selecting software -- Communication : do I have to learn a new language? -- Determining a staffing model -- Assessing the costs : budgeting for virtual reference -- Collaborative virtual reference -- Aspects of training -- Marketing your virtual reference service -- Assessment and evaluation : how are we doing? -- The road ahead : next steps and emerging technologies.
Electronic reproduction.
Keywords: Electronic reference services (Libraries); Electronic books